Фауна нематод хмеля в Житомирской области - Михайлюков, В.С.; Сигарева, Д.Д. (Вестник зоологии, 1981)
35 hop nematode species are revealed belonging to 27 genera, 12 families, 4 orders and 2 subclasses. A group of phytohelminths of a specific pathogenic effect is represented by 5 species among which Ditylenchus humuli is the most harmful. It affects germinal roots of the hop, which leads to their rotting and dying off. Necrosis of these organs is also induced by ectoparasite Tylenchorhynchus dubius. Heterodera humuli dominates in young fibrillose rootlets. Pratylenchus pratensis and Aglenchus agricola have no practical significance as the hop pests because their amount during the vegetation is low.